Deshonra (Daniel Tinayre, 1952): propaganda, lesbianismo, dicotomías y metáforas - Gijón, Pablo Rubio (Acta Hispanica, 2017)
Within the context of the film industry of the first peronist period (1946-1955) crime films established themselves as a means to disseminate the dominant ideology. Some of the characteristics of this genre were used to leave proof of the pre-eminence of the State as a safeguard of the status quo. However, Deshonra (1952) resorts in its structure to visual features that could be interpreted as a veiled criticism to the very ideology it aims to divulge. The crime film genre, from its constitutive proposals and its supposed ideological rigidity in a political framework such as Peronism, may grant some areas of ambiguity.